A Protocol for Examining and Mapping Elder Abuse Pathways in Iowa - Leonard A. Sandler; Brian Kaskie (Washington University Journal of Law & Policy, 2019)
This study and report is intended to guide and empower rural communities to map out, evaluate, and bolster the network of organizations, advocates, and governments to help combat elder abuse and neglect in all forms. It is the result of an in-depth examination of the discrete points in the east-central Iowa corridor, which generated several insights and recommendations. Many of the impediments stem from a lack of funding, and not from a lack of motivation, commitment, or effort from the three pillars of the Iowa system, Heritage Area Agency on Aging providers, Adult Protective Service workers, and law enforcement. Key informants urge cities and counties to earmark tax dollars, victim assistance funds, and civil monetary penalty funds to pay for local pilot projects, including enhanced multidisciplinary teams. Renewed focus could be placed on: dispelling myths and misconceptions surrounding elder abuse; increasing public awareness of the local organizations and people involved in identifying, reporting, responding to, and resolving incidents of abuse; acknowledging that no one person or organization can do it all alone, and encouraging systems agents to begin changing their culture and protocols; involving additional social workers and therapists in the system to address the complex family dynamics and relationships that are often at the heart of elder abuse; providing increased and easier access to persons qualified to assess an elder’s mental health and capacity for making decisions; funding for state and county attorneys to increase prosecution, increase state and local level specialized elder abuse units, and provide state-wide training of special prosecutors to handle elder abuse cases; and providing funding for individuals or organizations who are willing and available to make decisions for an elder, such as a financial or healthcare agent, guardian, conservator, Social Security Representative Payee, or other fiduciary.
Keywords: Elder law; elder abuse; public health; Iowa; rural communities